ZIEGLER, K; BARANGER, D. y BRADLEY, A. (Eds.) (2007). Constitutionalism and the role of Parliaments. Hart Publishing (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2008)
Recensión de la obra: ZIEGLER, K; BARANGER, D. y BRADLEY, A. (Eds.) (2007). Constitutionalism and the role of Parliaments. Hart Publishing.